Teacher's Ability To Implement Thematic Learning Variations In Grade IV At MI Islamiyah Pabuaran Cirebon - Safikri Safikri Taufiqurrahman; Ahmad Syarifuddin; Mamlatul Hikmah (Genderang Asa: Journal of Primary Education, 2026)
The ability of teachers to implement variations in learning is an alternative solution to overcome challenges in the teaching and learning process. This research describe the teacher’s ability in implementing variations in thematic learning on the topic of various energy sources for Grade IV students (identify students’ responses and analyze the obstacles faced by teachers in applying learning variations).This research employed a descriptive qualitative method. The research subjects included the school principal, classroom teacher, and Grade IV students. Data were collected through observation, interviews, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The study indicate that: (1) the teacher’s ability to implement variations in thematic learning is categorized as good, as evidenced by indicators such as voice variation, teaching style, and improved teacher-student interaction, which positively affect students’ learning motivation and evaluation outcomes; (2) students showed enthusiastic and active responses during the learning process, where they were not only passive recipients but also actively expressed opinions and engaged in learning based on their interests and abilities, resulting in a more dynamic classroom atmosphere; and (3) the obstacles faced by teachers include the diverse characteristics of students, which make classroom management challenging, as well as the extensive amount of material integrated into thematic learning, limiting the implementation of varied teaching strategies. Teachers’ ability to apply learning variations plays a significant role in enhancing student engagement and learning effectiveness, although it still faces several practical challenges in its implementation.